Biodegradation Behavior of Ozonated Natural Organic Matter in Sand Filters - Wang, J.; Summers, R. (Revue des sciences de l'eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 1996)
Natural organic matter (NOM) in drinking water is a complex mixture of organic compounds. Some of the compounds are not biodegradable, while others are quickly biodegradable and a third group is more resistant to biodegradation. To have a better understanding of the biofiltration process in drinking water treatment, it is important to identify the elements of the quickly and slowly biodegradable NOM and to characterize the biodegradation rate of each element. In this study, an ozonated NOM solution was used as the substrate. The NOM was isolated from a groundwater in Germany using ion-exchange resins. The ozone dose was 0.35 mg O3/mg DOC (dissolved organic carbon). Previously bioacclimated sand was used as filter media and biomass source and was homogeneously distributed in the filter prior to each run. The substrate removal was evaluated by DOC, biodegradable DOC (BDOC), assimilable organic carbon (AOC), aldehyde and ketoacid analyses. When expressed in terms of the empty bed contact time (EBCT), the results showed that filter velocity in the range of 1.5 to 15 m/hr had no impact on substrate removal. This implies that substrate utilization, not external mass transfer, is the rate limiting step for substrate removal in drinking water biofilters. In this study, compounds or NOM fractions are termed quickly biodegradable if they are removed in the first three minutes of EBCT. 15% of the DOC was removed by the biofilter within three minutes of EBCT and was termed the quickly biodegradable fraction. The BDOC fraction of the ozonated solution was determined to be 40 to 45% of the DOC. In terms of BDOC, about one third of the total BDOC was quickly biodegradable. The AOC results show that about 90% of the total AOC was utilized by Spirillum sp. NOX (AOC-NOX). Most of the AOC was quickly biodegradable and was removed within one minute of EBCT. For aldehydes, glyoxal and methyl glyoxal were removed to below the detection limit after two minutes of EBCT. However, only 60% of formaldehyde removal was achieved in the first two minutes of EBCT, and no additional removal was achieved with increasing EBCT. Additionally, no significant removal of acetaldehyde was observed. The results of ketoacids show that their utilization rates were very high. More than 90% of glyoxylic acid and pyruvic acid were removed within one minute of EBCT.